Kedudukan Hukum Salinan Akta Notaris dari Minuta Akta yang Belum Lengkap dalam Perspektif Prinsip Kehati-hatian - Purnama sari, Ayu (Recital Review, 2022)
This study aims to analyze the position of the copy of the deed and the minutes of deed according to the precautionary principle and to find out the legal implications of the copy of the deed from the incomplete deed from the perspective of the precautionary principle. The formulation of the problem in this research is how the position of the copy of the deed and the minutes of the deed according to the precautionary principle and what are the legal implications of the copy of the deed from the incomplete deed from the perspective of the precautionary principle. The research’s approaching method that will be used in this research is normative juridical based on the ambiguity of legal norms contained in Law No. 2 of 2014 concerning the position of a notary, Article 16 paragraph (1) letter a. This type of research data is secondary data consisting of primary, secondary, and tertiary legal materials. The data sources were then analyzed qualitatively. Based on the results of the study, it can be concluded that the position of the copy of the deed and the minutes of the deed according to the precautionary principle can be used as perfect evidence if the process of making the deed meets the formal and material requirements of the authentic deed and the procedures for making the deed as stipulated in the Notary Position Act. The legal implication of a deed copy of an incomplete deed from the perspective of the precautionary principle is that the deed has been degraded, in which it becomes a private deed and is null and void. It is recommended that the Notary in carrying out his duties must always apply the precautionary principle in every deed he makes. Thoroughly examine and observeÂ every statement, data, document, and letter used as the basis for making the deed, even though the notary has no obligation to ensure the authenticity of all of these things. Â Abstrak Penelitian ini bertujuan untuk mengetahui dan menganalisa kedudukan salinan akta dan minuta akta menurut prinsip kehati-hatian serta untuk mengetahui implikasi hukum salinan akta dari minuta akta yang belum lengkap dalam persfektif prinsip kehati-hatian. Adapun rumusan masalah dalam penelitian ini adalah bagaimana kedudukan salinan akta dan minuta akta menurut prinsip kehati-hatian dan bagaimana implikasi hukum salinan akta dari minuta akta yang belum lengkap dalam persfektif prinsip kehati-hatian. Metode pendekatan penelitian yang akan digunakan dalam penelitian ini adalah Yuridis Normatif atas dasar kekaburan norma hukum yang terdapat dalam Undang-Undang No 2 tahun 2014 tentang jabatan notaris Pasal 16 ayat (1) huruf a. Jenis data penelitian ini adalah data sekunder yang terdiri dari bahan hukum primer, sekunder, dan tersier. Data atau bahan yang telah diperoleh dianalisa secara kualitatif. Berdasarkan hasil penelitian dapat disimpulkan bahwa kedudukan salinan akta dan minuta akta menurut prinsip kehati-hatian dapat digunakan sebagai alat bukti yang sempurna jika proses pembuatan akta tersebut memenuhi persyaratan formal dan materiil akta otentik dan tata cara pembuatan akta yang tertuang dalam peraturan Undang-undang Jabatan Notaris. Implikasi hukum salinan akta dari minuta akta yang belum lengkap dalam persfektif prinsip kehati-hatian adalah akta tersebut mengalami degradasi yaitu menjadi akta di bawah tangan dan batal demi hukum. Disarankan agar Notaris dalam menjalankan tugasnya harus untuk selalu menerapkan prinsip kehati-hatian dalam setiap akta yang dibuatnya. Meneliti dan memeriksa dengan cermat setiap keterangan, data, dokumen, dan surat yang digunakan sebagai dasar pembuatan akta, meskipun notaris tidak memiliki kewajiban untuk memastikan keaslian semua hal tersebut